Efektifitas Layanan Konseling Individual Dalam Membantu Mengatasi Perilaku Membolos Siswa Kelas IX SMPN 22 Kota Jambi - Suci Gusti Lota (Prodi Bimbingan dan Konseling Islam (BPI) Fakultas Dakwah UIN Sulthan Thaha Saifuddin Jambi, 2020)
This research is motivated by the phenomenon of students in SMP Negeri 22 Jambi City ditching. This phenomenon needs special handling by the school. Besides ditching, many students don't speak the truth. Through the use of individual counseling which has a big influence on the improvement of students, the author aims to find out how the implementation of individual counseling services in SMPN 22 Jambi city, how effective individual counseling in helping to overcome truant behavior, and what are the factors of the effectiveness of individual counseling in helping to overcome truant behavior in SMPN 22 Jambi City. The research method is descriptive qualitative. The subjects in this study were students who played truant behavior and had received 5 individual counseling services. Data collection techniques used in this study were interviews, observation, and documentation. Interviews were conducted with 12 informants, observations in January to February 2020, while documentation was carried out during interviews and observations, were made. The researcher found in this study that the counseling implementation at SMPN 22 Kota Jambi was carried out well. This is because counseling services are carried out with the right procedures and techniques by BK teachers. The results of this study found that the effectiveness of individual counseling services in helping to overcome the truant behavior of students effectively seen from the absent odd and even semester of students who do truant behavior. This effectiveness is influenced by factors, namely: the factor of the supervising teacher, students, facilities, and infrastructure as well as time.